Corticospinal Tract in Newborns - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The maturation and function of the corticospinal and corticobulbar tracts in the human newborn are reviewed from the Departments of Paediatrics, Pathology and Clinical Neurosciences, University of Calgary Faculty of Medicine, Calgary, Alberta, Canada.